(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1852)
The secretary exhibited lithographs of sculptured standing stones with especial attention paid to the stone at Golspie, which had an Ogham inscription around its margin. He drew comparisons to the inscription on the Newton Stone, which was then revealed to be of even greater interest because it appeared to be a bilingual transcription. What follows is a summary of the activities at the Conversazione held on Feb. 26, 1852.